Cardiovascular Risk and Hippocampal Thickness in Alzheimer's Disease. (21st October 2013) - Donix, Markus; Scharf, Maria; Marschner, Kira; Werner, Annett; Sauer, Cathrin; Gerner, Antje; Nees, Josef A.; Meyer, Shirin; Donix, Katharina L.; Von Kummer, Rüdiger; Holthoff, Vjera A.
Abstract : Cardiovascular risk factors influence onset and progression of Alzheimer's disease. Among cognitively healthy people, changes in brain structure and function associated with high blood pressure, diabetes, or other vascular risks suggest differential regional susceptibility to neuronal damage. In patients with Alzheimer's disease, hippocampal and medial temporal lobe atrophy indicate early neuronal loss preferentially in key areas for learning and memory. We wanted to investigate whether this regional cortical thinning would be modulated by cardiovascular risk factors. We utilized high-resolution magnetic resonance imaging and a cortical unfolding technique to determine the cortical thickness of medial temporal subregions in 30 patients with Alzheimer's disease. Cardiovascular risk was assessed using a sex-specific multivariable risk score. Greater cardiovascular risk was associated with cortical thinning in the hippocampus CA2/3/dentate gyrus area but not other hippocampal and medial temporal subregions. APOE genotype, a family history of Alzheimer's disease, and age did not influence cortical thickness. Alzheimer's disease-related atrophy could mask the influence of genetic risk factors or age on regional cortical thickness in medial temporal lobe regions, whereas the impact of vascular risk factors remains detectable. This highlights the importance of cardiovascular disease prevention and treatment in patients with Alzheimer's disease.